“It’s not just any teaching program”: The new professionalism, educational inequity and Ako Mātātupu: Teach First New Zealand - Ramsey, Zachary; McFeely, Helen; Cusimano, Jackie; Crawford-Garrett, Katherine (Education Policy Analysis Archives, 2022)
In an effort to understand the impact of the international education network, Teach for All, this paper focuses on one Teach For All affiliate program, Ako Mātātupu/TFNZ (AM/TFNZ), to consider how Teach For All and its affiliates are reshaping notions of teacher expertise and professionalism as it defines itself in contrast to university-based teacher education. By drawing on qualitative data, including semi-structured interviews, participant observation, and document analysis, we argue that AM/TFNZ develops a new kind of professional by shifting 1) the purpose of becoming educators 2) the content of teacher education, and 3) the role of teacher educators. Ultimately, AM/TFNZ develops their educators outside of the literature, expertise, or histories of teacher education with a focus on creating a network of innovators capable of disrupting the status quo.